1980
DOI: 10.1152/ajpheart.1980.239.6.h794
|View full text |Cite
|
Sign up to set email alerts
|

Contractile function in canine right ventricle

Abstract: Regional right ventricular (RV) motion was examined in six acutely instrumented dogs by implanting radiopaque markers in three regions of the free wall: the apex, the midventricle, and the outflow tract. These markers were filmed at the paced heart rate of 180 beats/min with a high-speed biplane X-ray system, and their motion was analyzed with a digital computer. Local deformation was separated into percent length changes in the two mutually perpendicular principal directions. The major component exhibited sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 0 publications
8
45
0
Order By: Relevance
“…The amount of maximum strain measured (on average about 17%) was similar to previously measured RV strains in the conscious dog, 3,18,23 despite the substantially slowed heart rate in the anesthetized mouse in this study (250 bpm) compared with a conscious mouse (500-600 bpm). The literature contains conflicting results regarding regional strain differences.…”
Section: Regional Systolic Functionsupporting
confidence: 86%
See 1 more Smart Citation
“…The amount of maximum strain measured (on average about 17%) was similar to previously measured RV strains in the conscious dog, 3,18,23 despite the substantially slowed heart rate in the anesthetized mouse in this study (250 bpm) compared with a conscious mouse (500-600 bpm). The literature contains conflicting results regarding regional strain differences.…”
Section: Regional Systolic Functionsupporting
confidence: 86%
“…We found that strains were somewhat lower in the sinus region than the outflow tract region, which is consistent with some previous studies, 3,21 but disagrees with others. 18,27 The reasons for these discrepancies are not clear, but are likely due to differences in preparation such as in marker placement and open-vs. closed-chest measurements. RV pressure has been measured frequently in mice using similar methods in recent years, and developed pressures ranged between 8 and 30 mmHg, 6,29 possibly depending on the type and amount of anesthetic used.…”
Section: Regional Systolic Functionmentioning
confidence: 99%
“…28 26 Our results provide evidence that segment shortening is affected differently by acute pulmonary microembolisation in right ventricular inflow and outflow tracts. While shortening was not affected in the inflow tract, it decreased in the outflow tract.…”
Section: Segment Shorteningmentioning
confidence: 60%
“…One-dimensional relative motion data has been gathered by tracking pairs of radiopaque beads tracked with biplane cineradiography [30,51) or pairs of crystals with ultrasound [28]. By implanting several markers close together on the same ventricular surface (e.g., endocardium), researchers have been able to derive biaxial, or in-plane, deformations [17,6,341. The human RV has been studied using the noninvasive MRI tissue tagging method.…”
Section: Related Workmentioning
confidence: 99%